Edukasi Literasi Keuangan Untuk Anak-anak Panti Asuhan Muda Kartika - Tina Novianti Sitanggang; Ronald Hasudungan Rajagukguk; Jhon Lismart Benget. P; Riadi Riadi (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
Kartika Muda Orphanage, is one of the children's orphanages in Medan City, North Sumatra, located at Jalan Sunan Kalijaga/ Ampera Manunggal Pasar 6. Kartika Muda Orphanage has 25 children with an age range of 6 - 15 years. The aim of this service is to improve the financial literacy skills of the children of the Kartika Youth Orphanage through an introduction to money and its functions, an introduction to financial institutions and the concept of saving. In this service, the PKM Team found that the children of the Kartika Youth Orphanage did not know how to manage their finances well and did not have awareness of the importance of saving.